Teaching the Crisis: A Primer. (October 2014) - Granter, Edward; Tischer, Daniel
In this article, we provide a 'road map' for teaching the global economic crisis (the Crisis hereafter) sociologically, using Kindleberger's schema of financial crises. The causes of the Crisis are often associated with financial and economic technicalities, and we provide readers who are unfamiliar with the jargon of Collateralized Debt Obligations and Credit Default Swaps with a summary of the role played by these and other financial products. We seek to situate technical finance within the sociological frame of reference, where rationality and reality are areas of contention, rather than mathematical certainty. The article seeks, throughout, to foreground the social processes behind the credit bubble which burst in 2007. We argue for an understanding of the Crisis which takes into account the social totality, taking in culture, ideology and discourse, as well as political economy.